2017
DOI: 10.1021/acs.jctc.7b00089
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the AMOEBA Water Model in the Vicinity of QM Solutes: A Diagnosis Using Energy Decomposition Analysis

Abstract: The importance of incorporating solvent polarization effects into the modeling of solvation processes has been well-recognized, and therefore a new generation of hybrid quantum mechanics/molecular mechanics (QM/MM) approaches that accounts for this effect is desirable. We present a fully self-consistent, mutually polarizable QM/MM scheme using the AMOEBA force field, in which the total energy of the system is variationally minimized with respect to both the QM electronic density and the MM induced dipoles. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 181 publications
1
43
0
Order By: Relevance
“…This is likely why modified Poisson Boltzmann treatments/DFT 58 and classical/quantum DFT approaches 56 and recent hybrid and double hybrid functionals which incorporate some percentage of exact exchange, are addressing better QM accuracy 61 , and new approaches have been introduced that incorporate true many-body polarization effects across the QM/MM boundary. 62,63 This line of research has allowed for accurate rate constant prediction for molecule-surface reactions 64 , while Piccini et al showed how energy barriers for large systems like zeolites (over 1000 atoms) could be calculated within chemical accuracy (within 4 kJ/mol) using Density Functional Theory (DFT) methods. 65 But there are still significant difficulties for metal catalysts, for example metalloenzymes, where there may be multiple reactive sites requiring a QM description 66 , and for which errors in relative free energies do not generally fall below 20 kJ/mol due to poor accounting of strong correlation using DFT 67 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…This is likely why modified Poisson Boltzmann treatments/DFT 58 and classical/quantum DFT approaches 56 and recent hybrid and double hybrid functionals which incorporate some percentage of exact exchange, are addressing better QM accuracy 61 , and new approaches have been introduced that incorporate true many-body polarization effects across the QM/MM boundary. 62,63 This line of research has allowed for accurate rate constant prediction for molecule-surface reactions 64 , while Piccini et al showed how energy barriers for large systems like zeolites (over 1000 atoms) could be calculated within chemical accuracy (within 4 kJ/mol) using Density Functional Theory (DFT) methods. 65 But there are still significant difficulties for metal catalysts, for example metalloenzymes, where there may be multiple reactive sites requiring a QM description 66 , and for which errors in relative free energies do not generally fall below 20 kJ/mol due to poor accounting of strong correlation using DFT 67 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…This is probably for the trivial reason that the AMOEBA force field is now imbalanced with the introduction of the new physics that essentially assumes a wholly different charge distribution than the one assumed by Thole damping, and a total reparameterization would have to be undertaken to account for the different charge distribution. Furthermore, it is known that separating the nuclear and electron charges and smearing only the latter makes the issue of the missing exchange effect in polarization more pronounced, 91 which could otherwise curb the overpolarization observed in the short range. The main conclusion from the charge penetration analysis is that we can proceed with the analysis of the AMOEBA polarization against the ALMO-EDA polarization using the original Thole prescription for charge distribution, since the error in the permanent electrostatic field arising from point multipoles does not dominate the polarization errors.…”
Section: Figures 4 and S2 Show Unambiguously That Either Monopole Chamentioning
confidence: 99%
“…Our recent work [ 133 ] analytically showed that significant additional computational costs can be justified in multi-scale free energy simulations, if the sampling method exhibits a higher phase space overlap with the target QM Hamiltonian. Thus, it can be expected that polarizable force fields and, ultimately, quantum-mechanical methods will play an increasing role in free energy calculations [ 134 , 135 , 136 , 137 , 138 , 139 ].…”
Section: Introductionmentioning
confidence: 99%